2022
DOI: 10.3390/nano12234345
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Properties against SARS-CoV-2 of Nanostructured ZnO Obtained by Green Combustion Synthesis and Coated in Waterborne Acrylic Coatings

Abstract: The COVID-19 pandemic has increased the need for developing disinfectant surfaces as well as reducing the spread of infections on contaminated surfaces and the contamination risk from the fomite route. The present work reports on the antiviral activity of coatings containing ZnO particles obtained by two simple synthesis routes using Aloe vera (ZnO-aloe) or cassava starch (ZnO-starch) as reaction fuel. After detailed characterization using XRD and NEXAFS, the obtained ZnO particles were dispersed in a proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The Near Infrared spectra were also obtained for the pigments applied in waterborne acrylic paint to evaluate the performance of the pigments in a coating ( Figure 7 ). The commercial paint used in this study contains the white pigment titanium dioxide, as observed in our previous work [ 35 ], which can influence the NIR reflectance of the surface coatings due to its high solar reflectivity [ 5 ]. The NIR solar reflectance curves of the coatings were calculated by ASTM standard G173-03 ( Figure 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…The Near Infrared spectra were also obtained for the pigments applied in waterborne acrylic paint to evaluate the performance of the pigments in a coating ( Figure 7 ). The commercial paint used in this study contains the white pigment titanium dioxide, as observed in our previous work [ 35 ], which can influence the NIR reflectance of the surface coatings due to its high solar reflectivity [ 5 ]. The NIR solar reflectance curves of the coatings were calculated by ASTM standard G173-03 ( Figure 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained of the authors in [59] provide evidence that paint layers containing galvanic microcells of zinc and copper with a total copper surface area of 4.4% display virucidal activity according to ISO 21702 standard with human coronavirus NL63 as a model organism. In [60], antimicrobial coatings were developed from pure ZnO particles that reduce the infectivity of SARS-CoV-2 suspensions by >99.9% in 1 h. The study in [61] evaluates the high virucidal activity of acrylic paint surfaces painted with nanostructured ZnO-aloe pigments with a 10 wt.%. ZnO mass ratio against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%